(Z)‐3‐hexenol primes callose deposition against whitefly‐mediated begomovirus infection in tomato. (21st September 2022) - Yang, Fengbo; Zhang, Xinyi; Xue, Hu; Tian, Tian; Tong, Hong; Hu, Jinyu; Zhang, Rong; Tang, Juan; Su, Qi
SUMMARY: Rapid callose accumulation has been shown to mediate defense in certain plant–virus interactions. Exposure to the green leaf volatile ( Z )‐3‐hexenol ( Z ‐3‐HOL) can prime tomato ( Solanum lycopersicum ) for an enhanced defense against subsequent infection by whitefly‐transmitted Tomato yellow leaf curl virus (TYLCV). However, the molecular mechanisms affecting Z ‐3‐HOL‐induced resistance are poorly understood. Here, we explored the mechanisms underlying Z ‐3‐HOL‐induced resistance against whitefly‐transmitted TYLCV infection and the role of callose accumulation during this process. Tomato plants pre‐treated with Z ‐3‐HOL displayed callose priming upon whitefly infestation. The callose inhibitor 2‐deoxy‐d ‐glucose abolished Z ‐3‐HOL‐induced resistance, confirming the importance of callose in this induced resistance. We also found that Z ‐3‐HOL pre‐treatment enhanced salicylic acid levels and activated sugar signaling in tomato upon whitefly infestation, which increased the expression of the cell wall invertase gene Lin6 to trigger augmented callose deposition against TYLCV infection resulting from whitefly transmission. Using virus‐induced gene silencing, we demonstrated the Lin6 expression is relevant for sugar accumulation mediated callose priming in restricting whitefly‐transmitted TYLCV infection in plants that have been pre‐treated with Z ‐3‐HOL. Moreover, Lin6 induced the expression of the callose synthase gene Cals12, which is also required for Z ‐3‐HOL‐induced resistance of tomato against whitefly‐transmitted TYLCV infection. These findings highlight the importance of sugar signaling in the priming of callose as a defense mechanism in Z ‐3‐HOL‐induced resistance of tomato against whitefly‐transmitted TYLCV infection. The results will also increase our understanding of defense priming can be useful for the biological control of viral diseases. Significance Statement: Callose accumulation has been shown to mediate defense in certain plant–virus interactions, but few studies have elucidated the role of callose in restricting virus infection in primed plants. This study reveals a previously unrecognized role of callose priming in restricting Tomato yellow leaf curl virus infection in tomato resulting from whitefly transmission when the green leaf volatile Z‐3‐hexenol is used as a priming stimulus.